APPLICATION OF ARTICLE 42 PARAGRAPH (4) PP NO. 24 OF 1997 CONCERNING REGISTRATION OF TRANSFER OF RIGHTS DUE TO INHERITANCE IN THE EVENT OF AN INHERITANCE DISTRIBUTION IN MALANG RAYA - Intan Tresna Sari Rosita; Imam Kuswahyono; Hariyanto Susilo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The problem of transitional registration is one example of a land case that often occurs. Registration of transfer of rights due to inheritance is currently not understood equally by the government, especially in the implementation of registration of transfer of rights due to direct inheritance with the deed of distribution of inheritance. For this reason, this paper will try to conduct a legal study regarding effectivenessArticle 42 paragraph (4) Government Regulation Number 24 of 1997 concerning Land Registration, as the legal basis for carrying out transitional registration at Land Offices throughout Malang Raya. This paper uses the socio-legal method with an empirical and normative approach. The results showed that the registration of the transfer of rights due to direct inheritance with the deed of distribution of inheritance based on Article 42 paragraph (4) of Government Regulation Number 24 of 1997 concerning Land Registration did not work effectively at the Land Office in Malang Raya. There are several reasons, first, administrative habits that have been carried out in this wayfirst transfer of inheritance to all heirs based on a Statement of Heirs, then transfer to one of the heirs based on APHB. Second, the record problem. Third, the problem of local taxes that will be reduced.The ineffectiveness of this article can harm interested parties because it can be detrimental in terms of time and costs when registering the transfer of rights due to inheritance.